3,4,5-Tri-O-Caffeoylquinic Acid Promoted Hair Pigmentation Through β-Catenin and Its Target Genes - Bejaoui, Meriem; Villareal, Myra O.; Isoda, Hiroko (Frontiers in Cell and Developmental Biology, 2020)
The hair follicle undergoes a regular cycle composed of three phases: anagen, catagen, and telogen. The life of follicular melanocytes is totally linked to the hair cycle and during the anagen or the growth phase, the melanocytes are active and produce the melanin responsible for hair shaft pigmentation. Various signaling pathways regulate the hair growth cycle and therefore the pigmentation, we distinguish, the Wnt/β-catenin signaling pathway as it plays a major role in the development, growth, and proliferation of the melanocytes and the activation of melanogenesis enzymes and the related transcription factor. In this study, 3,4,5-tri-O-caffeoylquinic acid or TCQA a caffeoylquinic acid derivative stimulated the pigmentation in C3H mice, in human melanocytes, and B16F10 melanoma cells. An enhancement in pigmentation associated genes was observed upon TCQA treatment in vivo and in vitro. Interestingly, the expression of β-catenin was remarkably upregulated in mice treated skin and in pigment cells. Moreover, TCQA upregulated CTNNB1 expression after inhibition in human melanocytes. Taken together, this study suggests that TCQA triggered β-catenin activation to enhance the pigmentation during the anagen phase of the hair cycle.